Integrated electrical concentration and lysis of cells in a microfluidic chip - Church, Christopher; Zhu, Junjie; Huang, Guohui; Tzeng, Tzuen-Rong; Xuan, Xiangchun (Biomicrofluidics, 2010)
Lysing cells is an important step in the analysis of intracellular contents. Concentrating cells is often required in order to acquire adequate cells for lysis. This work presents an integrated concentration and lysis of mammalian cells in a constriction microchannel using dc-biased ac electric fields. By adjusting the dc component, the electrokinetic cell motion can be precisely controlled, leading to an easy switch between concentration and lysis of red blood cells in the channel constriction. These two operations are also used in conjunction to demonstrate a continuous concentration and separation of leukemia cells from red blood cells in the same microchannel. The observed cell behaviors agree reasonably with the simulation results.